ACCESS TO RESOURCES EFFECT ON FIRM PERFORMANCE: EVIDENCE FOR THE METAL-MECHANICAL INDUSTRY IN THE CONTEXT OF TERRITORIAL AGGLOMERATION (Desenvolvimento em Questão, 2020)
Access to resources are key factors for improving performance. This study aims to investigate the effect of access to resources on the firm performance in the metal-mechanical sector, in the context of territorial agglomeration. For that, a quantitative research, of the descriptive type, was carried out, being carried through a survey with 73 firm of the metal-mechanic sector. In the data analysis, the multiple linear regression technique was used. The results show that physical and organizational resources positively influence performance, whereas financial and human resources do not influence firm performance.
Keywords: Resources. Access to resources. Performance. Territorial agglomeration. Metal-mechanical industry.